Full-color capable light-emitting diodes based on solution-processed quantum dot layer stacking. Issue 14 (26th March 2018) - Lee, Ki-Heon; Han, Chang-Yeol; Jang, Eun-Pyo; Jo, Jung-Ho; Hong, Seungki; Hwang, Jun Yeon; Choi, Eunsoo; Hwang, Jin-Ha; Yang, Heesun
Abstract : An all-solution-processed full-color-capable white quantum dot-light-emitting diode was demonstrated by devising a novel emitting layer design of ZnO nanoparticle buffer-mediated B/G/R quantum dot layer stacking. Abstract : To date, most of the studies on quantum dot-light-emitting diodes (QLEDs) have been dedicated to the fabrication of high-efficiency monochromatic devices. However, for the ultimate application of QLEDs to the next-generation display devices, QLEDs should possess a full-color emissivity. In this study, we report the fabrication of all-solution-processed full-color-capable white QLEDs with a standard device architecture, where sequentially stacked blue (B)/green (G)/red (R) quantum dot (QD)-emitting layers (EMLs) are sandwiched by poly(9-vinylcarbazole) as the hole transport layer and ZnO nanoparticles (NPs) as the electron transport layer. To produce interlayer mixing-free, well-defined B/G/R QD layering assemblies via successive spin casting, an ultrathin ZnO NP buffer is inserted between different-colored QD layers. The present full-color-capable white QLED exhibits high device performance with the maximum values of 16 241 cd m −2 for luminance and 6.8% for external quantum efficiency. The promising results indicate that our novel EML design of ZnO NP buffer-mediated QD layer stacking may afford a viable means towards bright, efficient full-color-capable white devices.